The Improvement of Sugar Distribution System Using Value Stream Mapping (VSM) Approach A Case Study: Industri Gula Nusantara, Kendal, Jawa Tengah - Muchamad Muchfirodin; Henry Yuliando; Adi Joko Guritno (agriTECH, 2013)
This study was aimed to find kind of improvements of sugar distribution system using value stream mapping (VSM) when some inefficiencies in physical and service activities were encountered that will cause wasting time. The VSM was directed to reduce non value added time as the performace parameter. VSM was used to analyze thus inefficiencies because using VSM can simply mapping to trace whole activities both of material and service flow from beginning to the end of process. A case study of Industri Gula Nusantara showed that in its service operations, there were an inefficiency in the process of issueing the loading order. Move thus activity a day earlier, the improvement sounds a shorter service time over order and delivery schedule which in further make a better operation and service over the whole process of sugar distribution. At same time a policy of safety stock or inventory leveling could minimize stock out occasion by the increasing of service level from 25% to 38% that was close to standard deviation of demand during lead time.